2020
DOI: 10.1002/isd2.12139
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employees' resistance to change on implementing e‐government systems: An empirical study in Egypt

Abstract: Electronic government (e-government) implementation has played a key role in developing government business processes in order to improve efficiency in data processing, as well as achieving transparency and accuracy. However, although there are benefits of e-government implementation, there is the problem of employees' resistance to change, as people tend to resist any kind of new system. This research was conducted for the purpose of examining the effect of employees' resistance to change including resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
(50 reference statements)
0
20
1
2
Order By: Relevance
“…In fact, the changes or disruption to roles associated with information technology implementation is itself argued to lead to corruption (Elgohary and Abdelazyz, 2020). The integrity of digital systems is further eroded by regular security breaches; and the centralisation of biometric or identity data in national repositories increases the reward for external hackers, whilst creating almost 'infinite' opportunities for internal official misuse of personal data (Breckenridge, 2005: 281).…”
Section: Working Practicesmentioning
confidence: 99%
“…In fact, the changes or disruption to roles associated with information technology implementation is itself argued to lead to corruption (Elgohary and Abdelazyz, 2020). The integrity of digital systems is further eroded by regular security breaches; and the centralisation of biometric or identity data in national repositories increases the reward for external hackers, whilst creating almost 'infinite' opportunities for internal official misuse of personal data (Breckenridge, 2005: 281).…”
Section: Working Practicesmentioning
confidence: 99%
“…But it is also because information technology can amplify or create alternative opportunities for corruption, potentially of a much larger scale than the petty corruption prevalent in many African states (Donovan, 2015;Mutungi et al, 2019;Addo, 2021). In fact, the changes or disruption to roles associated with information technology implementation is itself argued to lead to corruption (Elgohary & Abdelazyz, 2020). The integrity of digital systems is further eroded by regular security breaches; and the centralisation of biometric or identity data in national repositories increases the reward for external hackers, whilst creating almost 'infinite' opportunities for internal official misuse of personal data (Breckenridge, 2005, p.281).…”
Section: Working Practicesmentioning
confidence: 99%
“…Adding new technologies to work practices can increase access to relevant data, but also leads to information overload for officials, affecting their perceived efficiency and effectiveness (Elgohary & Abdelazyz, 2020;Barata & Cain, 2001, p.255). A study of health information system adoption in two tertiary healthcare facilities in South Africa found that the broad, non-targeted adoption of computerised activities adds to workload for nurses, taking time away from patients -and so the recommendation is to more carefully target specific work flows for digitalisation (Cline & Luiz, 2013).…”
Section: Technical and Human Capabilitiesmentioning
confidence: 99%
“…Moreover, compared to less than 5 years of work experience or western group, respondents who have more than 5 years of experience or come from the Eastern region are more hesitant to learn the IVR training. Elgohary and Abdelazyz (2020) reported that there is a significant difference between the length of work experience and the resistance to change in a developing country setting. Given these observations, it is understandable that for these groups, EE is a more important factor to consider for IVR adoption intention than SI or HM.…”
Section: Theoretical Implicationsmentioning
confidence: 99%